Diagnostic and Management Approach of Obesity with Multiple Complications in a Child: A Case Report - Siti Azura Putri Dilla Sari; Cut Nurul Hafifah (The Indonesian Society of Pediatric Gastroenterology, Hepatology, and Nutrition, 2025)
Background: Adults with obesity may already experience obesity during childhood or adolescence, highlighting the critical importance of early intervention. This is particularly concerning given that childhood obesity, a growing component of Indonesia's